2015
DOI: 10.1074/jbc.m114.633107
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Tyrosine Kinase Pyk2 in Depolarization-induced Contraction of Vascular Smooth Muscle

Abstract: Background: Depolarization-induced tonic contraction of vascular smooth muscle involves tyrosine phosphorylation. Results: Depolarization activates the Ca 2ϩ -dependent tyrosine kinase Pyk2, leading to activation of the RhoA/Rho-associated kinase pathway. Conclusion: Activation of Pyk2 is required for the sustained phase of depolarization-induced contraction. Significance: Knowledge of the mechanisms responsible for sustained contraction is crucial for identification of defects leading to disease associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 29 publications
1
57
0
Order By: Relevance
“…Previous studies have shown that calcium can activate PYK2 by causing autophosphorylation at Tyr-402, a site that is required for kinase activity (33). Active PYK2 in vascular smooth muscle has been shown to mediate Ca 2+ /calmodulin-dependent PYK2 homodimer formation and transphosphorylation (35) and inhibit MYPT1 through a RhoA/ROCK pathway (36). Moreover, PYK2 inhibition has been shown to prevent stretch-induced activation of Akt and ERK1/2 (37).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that calcium can activate PYK2 by causing autophosphorylation at Tyr-402, a site that is required for kinase activity (33). Active PYK2 in vascular smooth muscle has been shown to mediate Ca 2+ /calmodulin-dependent PYK2 homodimer formation and transphosphorylation (35) and inhibit MYPT1 through a RhoA/ROCK pathway (36). Moreover, PYK2 inhibition has been shown to prevent stretch-induced activation of Akt and ERK1/2 (37).…”
Section: Discussionmentioning
confidence: 99%
“…-induced rat caudal arterial smooth muscle contraction in a concentration-dependent manner, and pretreatment of the tissue with salicylate eliminated the tonic component of depolarization-induced contraction without affecting the phasic contractile response (Fig. 4a) (Mills et al 2015). Likewise, salicylate abolished the sustained elevation of LC 20 phosphorylation without affecting the phasic K ?…”
Section: Identification Of the Tyrosine Kinase As Pyk2mentioning
confidence: 96%
“…Protein was extracted from each lyophilized tissue in 1 ml of SDS-gel sample buffer with constant shaking for 16 hours at 4°C. Tissue proteins were resolved by Phos-Tag SDS-PAGE and western blotting for the measurement of LC 20 , Par-4 and CPI-17 phosphorylation (Takeya et al, 2008;Moffat et al, 2011;Ihara et al, 2015), and by SDS-PAGE and western blotting with phosphospecific antibodies for MYPT1 phosphorylation (Grassie et al, 2012;Mills et al, 2015). For CPI-17, 12.5% acrylamide and 30 mM Phos-Tag reagent were used, and proteins were transferred to polyvinylidene difluoride (Roche Life Science, Quebec, Canada) overnight at 25 V and 4°C in 10 mM CAPS, pH 11, 10% methanol.…”
Section: Methodsmentioning
confidence: 99%
“…RhoA/ ROCK activation through Ga q/11 can result in contractile responses to PE; however, the functional linkages are incompletely understood (Puetz et al, 2009;Wettschureck and Offermanns, 2005). Moreover, KCl-induced membrane depolarization also elicits sustained contraction of VSM via activation of the RhoA/ROCK pathway (Mita et al, 2002(Mita et al, , 2013Sakamoto et al, 2003;Sakurada et al, 2003;Urban et al, 2003;Mills et al, 2015). The effects of inhibition of ZIPK during agonist-dependent contractions of caudal arterial smooth muscle suggest that the kinase lies downstream from GPCRs that signal through both Ga 12/13 and Ga q/11 (Fig.…”
mentioning
confidence: 99%